Barriers to Effective Teamwork Relating to Pediatric Resuscitations: Perceptions of Pediatric Emergency Medicine Staff. Issue 3 (March 2020) - Sherman, Joshua M.; Chang, Todd P.; Ziv, Nurit; Nager, Alan L.
Abstract : Background: In the pediatric emergency department (PED), resuscitations require medical teams form ad hoc, rarely communicating beforehand. Literature has shown that the medical community has deficiencies in communication and teamwork. However, we as medical providers do not know or understand the perceived barriers of our colleagues. Physicians may perceive a barrier that is different from nurses, respiratory therapists, pharmacists, or technicians. Perhaps we do not know in which area of teamwork and communication we are deficient. Only when we understand the perceptions of our fellow coworkers can we take steps toward improvement in quality resuscitations and therefore patient safety. Objective: The primary objectives of this study were to describe and understand the perceived barriers to effective communication and teamwork among different disciplines forming spontaneous resuscitation teams at a tertiary urban PED and to determine if providers of different disciplines perceived these barriers differently. Methods: This was a mixed-methods study conducted in a single, tertiary care freestanding children's hospital emergency department. Survey questions were iteratively developed to measure the construct of barriers and best practices within resuscitation teamwork, which was administered to staff among 5 selected roles: physicians, nurses, respiratory technicians, PED technicians, and PED pharmacists. It contained open-ended questions to provide statements on specific barriers or goals in effective teamwork, as well as a priority ranking on 25 different statements on teamwork extracted from the literature. From the participant data, 9 core themes related to resuscitation teamwork were coalesced using affinity diagramming by the authors. All statements from the survey were coded to the 9 core themes by 2 authors, with high reliability (κ = 0.93). Descriptive statistics were used to summarize the prevalence of themes mentioned by survey participants. A χ 2 test was used to determine differences in prevalence of core themes by role. Rank data for the 25 statements were converted to a point system (5 points for most important, 4 points for second most important, etc), and a mixed within-between analysis of variance was used to determine the association of role and relative rank. Results: There were 125 respondents (62% response rate) who provided 893 coded statements. The core theme of communication—in particular, closed-loop communication—was the most prevalent theme, although no differences in the proportion of themes represented were seen by PED staff of different roles ( P = 0.18). There was a significant effect from the core theme ( P = 0.002, partial η 2 = 0.13), with highest priority on team leader performance (mean points out of 5 = 2.5 ± 1.9), but neither effect nor interaction with role ( P = 0.6, P = 0.7). Conclusions: When answering open-ended questions regarding barriers to effective resuscitations, all disciplines perceived communication, particularly closed-loop communication, as the primary theme lacking during resuscitations. However, when choosing from a list of themes, all groups except physicians perceived deficiencies in team leader qualities to be the greatest barrier. We as physicians must work on improving our communication and leadership attributes if we want to improve the quality of our resuscitations.